(3OQGSGJ aj GdeMGSHI GdeJNUUI (B:s (3GdfXGe GdeMGSHj GdeGdj hfXGe eMGSHI GdJcGdja aj GdefTBJ GdNOejI (B"(3GdeSJTajGJ(B" /s - (3YWjI, gGTe CMeOs; (3YHO QHg eMeO, eMeO eMehO s ((3GdEScfOQjI(B: s (3GdOGQ GdLGeYjI(B, s, 2000)
(3YehejGJ(B:(3fXGe GdeYdheGJ hfTGW GdeSJTajGJ(B-(3GdfXGe GdeMGSHj aj GdeSJTajGJ(B-(3fXGe eMGSHI GdJcGdja aj GdeSJTajGJ(B-(3CSGdjH Jbjje GdCOGA aj GdeSJTajGJs
(3HHdjhZQGajG(B: (3U(B. 340s
Keywords: (3GdeSJTajGJs; (3GdeSJTajGJ(B-(3eMGSHIs; (3eMGSHI GdJcGdjas